Survival, male morphotypes, female and male proportion, female reproductive status and tag loss in crosses among three populations of freshwater prawn Macrobrachium rosenbergii (de Man) in India - Pillai, B.R.; Mahapatra, K.D.; Ponzoni, R.W.; Sahoo, L.; Lalrinsanga, P.L.; Mekkawy, Wagdy; Khaw, H.L.; Nguyen, N.H.; Mohanty, Samarendu; Sahu, S.; Patra, G. (Hindawi Limited, 2015)
The present study examined the variation in survival, proportion of male morphotypes, female and male proportion, female reproductive status and tag losses in nine crosses from a complete (3 × 3) diallel mating of three populations of Macrobrachium rosenbergii in India. The populations originated from Gujarat (north-west), Kerala (south-west) and Odisha (east), representing different agro-ecological regions in India. Progeny from 60 families (4773 juveniles) were individually tagged and reared for 16–17 weeks in earthen ponds. Binary logistic regression was used to analyse the data. Survival rate was greatest (0.88) for Kerala × Odisha (KO; the first letter represents the sire), whereas it was lowest (0.75) for both Kerala × Kerala (KK) and Gujarat × Kerala (GK). Significantly greater proportions of large male morphotypes were observed in KK cross and in combinations involving Kerala population. The highest proportion of immature females, as well as of non-berried females, was observed in the Odisha × Odisha (OO) cross. Tag loss was greatest for KK (0.35) and lowest for GG (0.19). We found significant variations among crosses for all studied traits suggesting the possibility of including them in genetic improvement programmes of this species.